(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The study investigates the influence of staff development programmes on job performance of Office Technology and Management (OTM) lecturers in polytechnics in Northwest, Nigeria. Two research questions guided the study, while two hypotheses were tested. Descriptive survey research design was used for the study. The population of the study was 177 OTM lecturers from public polytechnics in North West, Nigeria. The entire population was used. A structured 4-point sealed questionnaire containing 20 items in two clusters was used for data collection. Data were analyzed using mean and standard deviation to answer the research questions, while t-test was used in testing the hypotheses at 0.05 level of significance. Findings revealed that OTM lecturers in polytechnics in North-West Nigeria agreed that staff development programmes influenced their job performance. It was, therefore, recommended among others that, Tertiary Education Trust Fund (Tetfund), in collaboration with other educational stakeholders should make staff development programmes more accessible to OTM lecturers which will help them to improve their instructional planning.